Pengaruh Kepemimpinan dan Integritas terhadap Loyalitas Karyawan pada Kelurahan Semper Timur - Suci Widha Ramadhanti; Ana Ramadhayanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The background to this research is based on the importance of leadership and integrity in increasing employee loyalty, especially in the government sector. Employee loyalty is a key factor in creating a productive and harmonious work environment. This research aims to analyze the influence of leadership and integrity on employee loyalty in Semper Timur Subdistrict. The method used in this research is a quantitative approach by distributing questionnaires to 40 employees of Semper Timur Subdistrict. Data analysis was carried out using linear multiple regression to test the relationship between leadership, integrity, and employee loyalty variables. The research results show that both leadership and integrity have a significant influence on employee loyalty. Effective leadership and high integrity between leaders and employees have been proven to increase employee loyalty, which in turn has a positive impact on overall organizational performance.